Timeless Learning - Socol, Ira; Moran, Pam; Ratliff, Chad (Ascent Audio, 2019)
Our homes, communities, and the world itself need the natural assets our children bring with them as learners, and which they often lose over time on the assembly line that pervades most of the public education system today. We see no actions as more important in school than developing, supporting, and reinforcing children's sense of agency, the value of their voices, and their potential to influence their own communities. In Timeless Learning, an award-winning team of leaders, Chief Technology Officer Ira Socol, Superintendent Pam Moran, and Lab Schools Principal Chad Ratliff demonstrate how you can implement innovative practices that have shown remarkable success. The authors use progressive design principles to inform pathways to disrupt traditions of education today and show you how to make real innovations that will have a timeless and meaningful impact on students, keeping alive the natural curiosity and passion for learning with which children enter school. - Discover the power of project-based and student-designed learning - Find out what "maker learning" entails - Launch connected and interactive digital learning - Benefit from the authors' "opening up learning" space and time.